Invasive amphibians in southern Africa: A review of invasion pathways - Measey, John; Davies, Sarah J.; Vimercati, Giovanni; Rebelo, Alex; Schmidt, Warren; Turner, Andrew (African Biodiversity & Conservation, 2017)
Background: Globally, invasive amphibians are known for their environmental and social impacts that range from poisoning of local fauna and human populations to direct predation on other amphibians. Although several countries on most continents have had multiple introductions of many species, southern Africa appears to have escaped allochthonous introductions. Instead, it has a small number of domestic exotic species that have rapidly expanded their ranges and established invasive populations within South Africa. Objectives & methods: We used the literature to provide a historical overview of dispersal by some of the world’s major invasive amphibians, give examples of species that are commonly moved as stowaways and discuss historical and current amphibian trade in the region. In addition, we give an overview of new South African legislation and how this is applied to amphibian invasions, as well as providing updates on the introduced populations of three domestic exotics: Hyperolius marmoratus, Sclerophrys gutturalis and Xenopus laevis. Results: We show that frogs are mainly moved around southern Africa through ‘jump’ dispersal, although there are a number of records of ‘cultivation’, ‘leading-edge’ and ‘extreme long-distance’ dispersal types. Important pathways include trade in fruit and vegetables, horticultural products and shipping containers. Conclusion: We suggest that southern Africa is becoming more vulnerable to amphibian invasions because of an increase in trade, agricultural and domestic impoundments as well as global climate change. Increasing propagule pressure suggests that preventing new introductions will become a key challenge for the future. Currently, trade in amphibians in the region is practically non-existent, suggesting potential for best practice to prevent importation of species with high invasion potential and to stop the spread of disease.